2011
DOI: 10.1270/jsbbs.61.168
|View full text |Cite
|
Sign up to set email alerts
|

Histological and genetic characteristics associated with the seed-shattering habit of weedy rice (Oryza sativa L.) from Okayama, Japan

Abstract: We aimed to elucidate the molecular nature of the seed-shattering habit of weedy rice Oryza sativa L. in Okayama Prefecture, Japan, which seems to be an "off-type" of the main rice varieties in Okayama. We performed time-course analyses of breaking tensile strength (BTS) and analyzed the histological features of pedicels; we also genotyped the seed-shattering genes qSH1 and sh4 of weedy rice accessions and rice cultivars. The BTS of weedy accessions and cultivars began to decrease simultaneously at three weeks… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
17
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 23 publications
1
17
0
Order By: Relevance
“…The qSH1 gene is a major quantitative trait locus of grain shattering in rice and a single-nucleotide polymorphism in the promoter region of qSH1 gene causes loss of grain shattering owing to the absence of abscission layer formation (Konishi et al, 2006). Four rice cultivars with a relatively easily-shattering habit, Asahi, Akebono, Kibinohana and Omachi were reported to carry a functional qSH1 allele and a non-functional sh4 allele (Akasaka et al, 2011). In the present study, Asahi, Akebono, Kibinohana and Omachi showed the type A grain-shattering pattern dominantly.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The qSH1 gene is a major quantitative trait locus of grain shattering in rice and a single-nucleotide polymorphism in the promoter region of qSH1 gene causes loss of grain shattering owing to the absence of abscission layer formation (Konishi et al, 2006). Four rice cultivars with a relatively easily-shattering habit, Asahi, Akebono, Kibinohana and Omachi were reported to carry a functional qSH1 allele and a non-functional sh4 allele (Akasaka et al, 2011). In the present study, Asahi, Akebono, Kibinohana and Omachi showed the type A grain-shattering pattern dominantly.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, a medium-shattering cultivar has more sclerenchymatous fiber tissues around the vascular bundle as compared with the easily-shattering cultivar. Akasaka et al (2011) presumed that extremely easilyshattering trait of weedy rice accessions is mediated by unidentified genes other than qSH1 and sh4. Additionally, the data of Akasaka et al (2011) indicates that differences of grain shattering habit among these four cultivars (Asahi, Akebono, Kibinohana and Omachi) in Okayama are also mediated by unidentified genes other than qSH1, sh4 and other genes that regulate weedy shattering trait.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The persistence of weedy rice has been partly attributed to its ability to shatter seeds ) and it shows a wide variation in this seed shattering trait (Nunes et al 2014). Rice seeds shatter subsequent to the development of an abscission layer between the grain and pedicel (Akasaka et al 2011;Thurber et al 2011;Yan et al 2015). Shattering wild and weedy rice individuals possess well-defined abscission layers at flowering time, which are not present in domestic cultivars (Ferrero and Vidotto 1998;Thurber et al 2011;Akasaka et al 2011).…”
Section: Seed Shatteringmentioning
confidence: 99%